USE OF THE QUIZIZZ PAPER MODE APPLICATION AS A MEDIA IN BIOLOGY LEARNING EVALUATION - Elu, Katharina Gai; Jawa, Florentiana Ermelinda; Wae, Veronika P Sinta Mbia; Mode, Juliana (LPPM Universitas Flores, 2025)
Learning evaluation is the primary activity used to measure the achievement of abilities possessed by students. This action is important because it can function as a basis for determining subsequent learning policies. Evaluation has a different meaning from assessment and measurement. Evaluation is preceded by assessment, which in turn is preceded by measurement. Measurement can be interpreted as an activity to compare the results of observations or information on the characteristics of an object. Therefore, assessment is the most important process in determining the results of learning evaluation. To measure how well students' understanding and learning outcomes are, an effective tool is needed to carry out evaluations. The media that can be used for learning evaluation is Quizizz Paper mode, a technology-based application for carrying out learning evaluations. Quizizz with paper mode uses QR codes on sheets of paper that can be applied in offline learning, aiming to support teachers and students in creating creative face-to-face learning experiences through interactive quizzes, which are effective and efficient. This evaluation also indicates an increase in student participation due to the competitive and fun elements provided by Quizizz, even in paper format. This study proposes that the use of Quizizz in various modes can increase the effectiveness and participation of students in learning evaluations. Implementation of learning evaluation with the Quizizz application has proven to be easier, so that the evaluation process becomes more efficient and effective. This activity was carried out at Alsiora Ende Private High School with the aim of finding out the application of Quizizz in paper mode in biology learning as an evaluation medium.